Forest certification for promoting sustainable forestry in Nepal - Parajuli, Damodar P.; Kandel, Pem Narayan; Linforth, Vanessa (Banko Janakari, 2017)
Abstract on the PDF Banko Janakari Vol.13(2) 2003: 3-7